Psychometric Properties of the Test of Mobile Phone Dependence Brief (TMDBrief) in Peruvian College Students - Franco-Jimenez, Andrei; Garcia-Rivera, Melisa Yedit; Campos-Rosas, Rosa Maria (Interacciones, 2025)
Background: The increasing use of smartphones has raised concerns about problematic use and its impact on mental health. Assessing smartphone addiction requires valid and reliable instruments, such as the Test of Mobile Phone Dependence Brief (TMDbrief), which has been widely used in various cultural contexts. Objective: This study aimed to evaluate the psychometric properties of the TMDbrief, including its factorial structure, internal consistency, measurement invariance across gender, and convergent validity with depression and phubbing behaviors in Peruvian university students. Method: In this cross-sectional study, a sample of 954 students completed the TMDbrief, the PHQ-9 to assess depression, and the Phubbing Scale to measure phone-related social disruptions. Confirmatory factor analysis (CFA) tested the four-factor structure, and McDonald's omega assessed internal consistency. Measurement invariance across gender was examined to ensure the instrument's applicability in both male and female students. Result: CFA confirmed the four-factor structure (χ²(48) = 320.31, CFI = .983, TLI = .977, RMSEA = .077, SRMR = .029). Internal consistency was strong, with McDonald’s ω between .80 and .85; CR ranged from .80 to .86 and AVE from .57 to .67, indicating adequate convergence. Measurement invariance across gender was confirmed, and convergent validity was supported by moderate correlations with depression and phubbing behaviors. Conclusion: The TMDbrief is a valid and reliable instrument for assessing smartphone addiction among Peruvian university students, supporting its use in research, early detection, and intervention development.